The Use of Pentobarbital in Cases of Severe Delirium: A Case Series. (February 2014) - Kerr, Christopher W.; Luczkiewicz, Debra L.; Holahan, Timothy; Milch, Robert; Hang, Pei C.
Delirium is a common syndrome present at the end of life and causes significant distress for patients and families. Sleep disruption is a common precipitating factor for delirium and restoration of sleep may be instrumental in attenuating symptoms. In this cases series, we present three patients who were unresponsive to escalating doses of standard delirium medications, but whose delirium resolved once improved sleep was achieved using Pentobarbital. In a fourth patient, delirium was successfully treated where neuroleptics were contraindicated. Pentobarbital has been shown to reduce the time to sleep onset, decrease the number of body movements during sleep and spontaneous awakenings and increase the total sleep time. Pentobarbital may provide an additional treatment option for patients whose delirium is refractory to standard management approaches.